The Analysis of Pre-Service EFL Teachers’ Teaching Implementation - Lamhot Naibaho (Budapest International Research and Critics University, 2021)
This study discussed the pre-service EFL teachers' teaching implementation, and it was done to find out how the implementation of the Pre-service EFL teaching implementation was. This research was done at 3 Private Junior High schools in East Medan, in Pancing, Medan. The respondents of the study were 76 students who were chosen using the quota sampling technique. The instrument of the study used was a set of questionnaires that consisted of 25 statements items. The result of the study is that students were agreed with the Pre-service EFL teachers' teaching level quality (3.39), teaching level appropriateness (3.31), motivation and reward (3.22), and teaching time management (3.48). It is concluded that the Pre-service teachers' teaching implementation is at a moderate level.